2021
DOI: 10.18240/ijo.2021.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-29b found in aqueous humour mediates calcium signaling in diabetic patients with cataract

Abstract: AIM: To investigate the role of exosomal miR-29b and Ca2+ in regulating the function of human lens epithelial cells (HLECs). METHODS: Exosomes were isolated from human aqueous humour (AH) by ultracentrifugation, and visualized by nanoparticle tracking and transmission electron microscopy. Exosomal miRNA sequencing was performed to identify differentially expressed miRNAs between diabetes with cataracts (DMC) group and age-related cataracts (ARC) group. TargetScan was used to predict potential target of certain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In our previous study, we successfully isolated abundant exosomes from AH samples in the DMC and ARC groups and found that exosomal miRNAs could target the mRNAs of certain genes to affect the viability and apoptosis of human lens epithelial cells. For example, high expression of miR-551b could downregulate CRYAA expression, thus decreasing the transparency of the lens [ 26 ], and low expression of miR-29b could upregulate CACNA1C expression, resulting in an increased concentration of Ca 2+ in the AH of DMC eyes [ 27 ]. The miR-26a-5p/ITGAV/TGF-β/Smad3 axis was also reported to be involved in cell viability, migration and epithelial–mesenchymal transition in diabetic cataracts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we successfully isolated abundant exosomes from AH samples in the DMC and ARC groups and found that exosomal miRNAs could target the mRNAs of certain genes to affect the viability and apoptosis of human lens epithelial cells. For example, high expression of miR-551b could downregulate CRYAA expression, thus decreasing the transparency of the lens [ 26 ], and low expression of miR-29b could upregulate CACNA1C expression, resulting in an increased concentration of Ca 2+ in the AH of DMC eyes [ 27 ]. The miR-26a-5p/ITGAV/TGF-β/Smad3 axis was also reported to be involved in cell viability, migration and epithelial–mesenchymal transition in diabetic cataracts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…EM revealed EVs of an appropriate size but the presence of EV tetraspanins was not examined. Differences in the miRNA content of the different samples of AH-derived EVs were reported (C. Gao et al, 2021 ), but as noted above, the EV samples were not pre-treated with appropriate enzymes (RNAse, trypsin, proteinase K, see Valadi et al, 2007 ) to eliminate extravesicular contaminants, limiting what can be concluded with regards to biomarker discovery. In another study, Mass Spectrometry analysis of the EV cargo of AH-derived EVs from patients with AMD revealed elevated levels of apolipoprotein A1, C3 convertase, opticin and clusterin proteins, compared to healthy controls ( Tsai et al, 2022 ); the study did not perform RNA anlysis.…”
Section: Extracellular Vesicles As Potential Biomarkers Of Ocular Dis...mentioning
confidence: 99%
“…Specific miRNAs have been found in AH derived EVs from uveal melanoma patients (Luz Pessuti et al, 2022), while Gao et al, 2021 provide convincing evidence of the presence of EVs in AH fluids from patients with diabetes and cataracts (DMC), compared with patients with age-related cataracts (ARC) (C. Gao et al, 2021). EM revealed EVs of an appropriate size but the presence of EV tetraspanins was not examined.…”
Section: Extracellular Vesicles As Potential Biomarkers Of Ocular Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also noticed that mimics of miR-551b reduced the viability of HLECs drastically, and its inhibitors lessened the apoptosis of these cells ( Gao et al, 2021a ). Additionally, Gao et al (2021b) found that in exosomes isolated from AH, miR-29b was substantially downregulated in a DC cohort than an ARC cohort, thus triggering the expression of its potential target Calcium Voltage-Gated Channel Subunit Alpha1 C (CACNA1C). High CACNA1C level is associated with increased concentration of Ca 2+ inducing apoptosis of HLECs in patients with DC ( Gao et al, 2021b ).…”
Section: Cataractmentioning
confidence: 99%